2008
DOI: 10.1007/s10808-008-0086-3
|View full text |Cite
|
Sign up to set email alerts
|

Model of a strong discontinuity for the equations of spatial long waves propagating in a free-boundary shear flow

Abstract: The long-wave equations describing three-dimensional shear wave motion of a free-surface ideal fluid are rearranged to a special form and used to describe discontinuous solutions. Relations at the discontinuity front are derived, and stability conditions for the discontinuity are formulated. The problem of determining the flow parameters behind the discontinuity front from known parameters before the front and specified velocity of motion of the front are investigated. Introduction.We consider a mathematical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In the present section, use is made of the discontinuity relations obtained in [5] for the equations of stationary flows (1.2). It is shown that the set of states behind the jump is determined by some curve similar to the (θ, p)-polar curve in gas dynamics.…”
Section: Flows With Discontinuitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present section, use is made of the discontinuity relations obtained in [5] for the equations of stationary flows (1.2). It is shown that the set of states behind the jump is determined by some curve similar to the (θ, p)-polar curve in gas dynamics.…”
Section: Flows With Discontinuitiesmentioning
confidence: 99%
“…System (1.2) cannot be reduced to divergent form. In [5], it is proposed to use the following form of system (1.2), which is equivalent to the initial one for smooth solutions: (2.1)…”
Section: Flows With Discontinuitiesmentioning
confidence: 99%
See 3 more Smart Citations